PENGARUH PROMOSI GRATIS ONGKIR E-COMMERCE SHOPEE TERHADAP MINAT PEMBELI DI KECAMATAN DATUK BANDAR KOTA TANJUNGBALAI - Muammar Qhadavi Nasution; Suheri Harahap; Anang Anas Azhar (Lafadz Jaya Publisher, 2023)
This research is entitled The Influence of Shopee E-Commerce Free Shipping Promotion on Buyer Interest in Datuk Bandar District, Tanjungbalai City. Against Buyer Interest in Datuk Bandar District, Tanjungbalai City. Objective of this study is to determine the effect of E-commerce free shipping promotion at Shopee's free shipping promotion on buyer interest and to find out the increase in buying interest in Shopee's free shipping promotion. on the promotion of free shipping E-commerce Shopee on buyer interest in Datuk Bandar District, Tanjungbalai City. The theory used is the theory of Influence, Sales Promotion, E-commerce, Purchase Interest and AIDDA theory. Object The object studied was the community in Datuk Bandar District, Tanjungbalai City who do online shopping from Shopee. This research approach is using quantitative research methods and with the use of correlational correlational method which has the aim of finding the relationship between promotion and buying interest. buying interest. The data analysis technique uses single table analysis, cross table analysis and correlation test using the Spearman Rho formula through the SPSS application. cross table analysis and correlation test using the Spearman Rho formula through the SPSS 26 application. 26. The results of the hypothesis test show that ????0 is rejected and ????1 is accepted, with an influence strength of 55%. the strength of the influence is 55%. The result of this study is that the promotion of promotion of free shipping from Shopee e-commerce has an effect on buyer interest in Tanjungbalai city. Datuk Bandar sub-district, Tanjungbalai city.